Contact line instabilities of rotating, viscous droplets - Roper, Tom William (2024)
In this thesis, we investigated the stability of the contact line of an initially ax- isymmetric, fixed volume of viscous fluid upon a flat rotating disc, centred on the axis of rotation. We performed an experimental analysis, concerning the onset and formation of the instabilities at the contact line. The instability at the con- tact line is characterised by an integer number of fingers given by the dominant wavenumber, which is found to be proportional to both the volume and rotation rate in the investigated parameter range.